Analisis Faktor Kepuasan Konsumen di Shopee: Tinjauan Kualitas Sistem, Informasi, dan Layanan (Studi Kasus: Pada Pengguna Shopee di Daerah X) - Delia, Irene (PT Literasi Nusantara Publisher, 2025)
This study aims to analyze the influence of system quality, information quality, and service quality on consumer satisfaction among users of the Shopee e-commerce platform in Region X. Using a quantitative approach with a purposive sampling technique, data from 120 respondents were analyzed using multiple linear regression. The findings indicate that system quality, information quality, and service quality have a positive and significant influence on consumer satisfaction, both partially and simultaneously. Information quality was found to be the most dominant predictor, with the three quality variables collectively explaining 55.6% of the variability in consumer satisfaction. The originality of this study lies in testing an integrated quality model within a regional e-commerce context (Region X) and highlighting the dominance of information quality as a primary driver of satisfaction. The practical implication for Shopee is the need to prioritize strategies for improving information accuracy and completeness to maintain and enhance customer satisfaction in non-metropolitan areas, alongside maintaining system and service reliability.